UJARAN KEBENCIAN: PERSPEKTIF ILMU PSIKOLOGI - Gazi Saloom (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This article discusses about hate speech with systematic review method. All literatures related to hate speech were reviewed in depth way, then some of them were chosen particularly the most relevant to psychology science. Various concepts and theories were found able to explain the substance and the construct of hate speech. But it could be assisted that the concepts of prejudice and aggression were deemed as the most relevant to psychological matters